2020
DOI: 10.2147/cmar.s232357
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mediation Analysis Reveals Potential Biological Mechanism of Ascites Influencing Recurrence in Patients with Epithelial Ovarian Cancer</p>

Abstract: Objective: Ascites, an accumulation of peritoneal fluid, is associated with poor prognosis of certain cancers. The potential mechanism that ascites worsens prognosis has not been well understood. Lipids have been reported to correlate with the prognosis of patients with epithelial ovarian cancer (EOC). Therefore, we aimed here to investigate whether lipids mediate the effect of ascites on the recurrence of EOC. Methods: We collected the demographic and pathological data of 437 previously untreated patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The number of studies reported for each country is as follows (Fig. 4 b): 10 studies (26%) were reported from China [ 24 , 26 , 28 , 45 , 46 , 50 , 52 , 55 , 59 , 60 ], eight (21%) from Japan [ 31 , 37 – 39 , 41 43 , 53 ], four (11%) from the USA [ 30 , 33 , 47 , 48 ], two (5%) each from Australia [ 32 , 34 ], Brazil [ 29 , 61 ], and Germany [ 25 , 40 ], one (3%) each from Argentina [ 54 ], Canada [ 57 ], Czech [ 51 ], Finland [ 44 ], Italy [ 56 ], Netherlands [ 49 ], Portugal [ 36 ], Romania [ 27 ], Singapore [ 58 ], and Spain [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies reported for each country is as follows (Fig. 4 b): 10 studies (26%) were reported from China [ 24 , 26 , 28 , 45 , 46 , 50 , 52 , 55 , 59 , 60 ], eight (21%) from Japan [ 31 , 37 – 39 , 41 43 , 53 ], four (11%) from the USA [ 30 , 33 , 47 , 48 ], two (5%) each from Australia [ 32 , 34 ], Brazil [ 29 , 61 ], and Germany [ 25 , 40 ], one (3%) each from Argentina [ 54 ], Canada [ 57 ], Czech [ 51 ], Finland [ 44 ], Italy [ 56 ], Netherlands [ 49 ], Portugal [ 36 ], Romania [ 27 ], Singapore [ 58 ], and Spain [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were also two cases (5%) [ 36 , 60 ] where the details were not specified in the text. Within the software category, Analyst was the most frequently used in five cases (24%) [ 26 , 30 , 44 , 56 , 61 ], followed by Mass Hunter Qualitative Analysis in three cases (14%) [ 45 , 46 , 51 ]. ALEX [ 25 , 51 ], Metabolon [ 47 , 57 ], MS-DIAL [ 28 , 52 ], Progenesis QI [ 54 , 55 ] and LipidSearch [ 33 , 59 ] were used each in two cases (10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic-peritoneal cavity transcoelomic route is regarded as the typical way of EOC metastasis, which is widely believed to occur via peritoneal circulation of ascites [ 3 ]. Malignant ascites was a common complication of EOC and was reported to be an independent unfavorable prognostic factor of EOC [ 4 , 5 ]. Constant Malignant ascites led to metastasis [ 6 8 ], while the underlying mechanism needs more thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic-peritoneal cavity transcoelomic route is regarded as the typical way of EOC metastasis, which is widely believed to occur via peritoneal circulation of ascites (3). Malignant ascites was a common complication of EOC and was reported to be an independent unfavorable prognostic factor of EOC (4,5). Constant Malignant ascites led to metastasis (6-8), while the underlying mechanism needs more thorough investigation.…”
Section: Introductionmentioning
confidence: 99%